Growth performance, proximal composition of muscle and haematological parameters of juveniles Colossoma macropomum fed with an all plant-based diet in comparison to a low-fishmeal diet - Grande Fernández, Brenda Carolina (2023)
The aim of this study was to determine the effect of a vegetable diet compared to a diet containing fishmeal at the commercial level (6%) on body growth, proximal composition of fillets and hematological parameters of juvenil gamitana (Colossoma macropomum). The experiment followed a completely randomized design with two treatments, an exclusively vegetable diet and a diet with low fishmeal content (6%), and three 200 m3 dug earthen ponds as experimental units per treatment. A total of 1200 fish (172.9 g; 19.4 cm) distributed in the six ponds (1 fish/m3) were used. Feeding was done twice a day (08:00 and 16:00) at a daily feeding rate of 2% for 60 days. The water quality parameters were monitored daily and showed constant values and within the comfort range of the species. The exclusively vegetable diet had a similar effect as the fishmeal diet on body growth [final weight 258.9 g, weight gain 86.1 g, supplied feed 128.4 g, feed conversion 1.24, relative growth rate 1.74%/day, factor of condition 1.91, 0% mortality], the proximal composition of fillets [moisture 77.90%, ash 1.39%, protein 18.98%, lipid 0.86%], as well as in the hematological parameters. It is concluded that an exclusively vegetable diet can be used for the rearing of juvenile gamitana, contributing to the sustainability of its production and reduction of feeding costs.